Relationship between workload, psychological state and recovery in female soccer athletes - Long, J. W.; Brown, D.; Farrell, J.; Gonzalez, M.; Cheever, K. (International Journal of Sports Medicine, 2024)
This study assessed the multifaceted relations between measures of workload, psychological state, and recovery throughout an entire soccer season in female collegiate soccer athletes (19.8±1.2 yrs, 132±12.3 lbs, 63±3.2 in). A prospective longitudinal study was utilized to measure workload (GPS training load, Rate of Perceived Exertion (RPE), psychological state (mental stress, mental fatigue, and mood), and recovery (sleep duration, sleep quality, and soreness), during 90 observations (59 training sessions and 21 games). Separate linear-mixed effect models were used to assess outcomes of RPE, soreness, and sleep duration. A linear mixed-effects model explained 59% of the variance in RPE following each session. Specifically, each standard deviation increase in GPS load and mental stress in the morning prior to training increased RPE by 1.46 (SE=0.08) and 0.29 (SE=0.07), respectively, following that day`s training. Furthermore, a significant interaction was found between several predictor variables and chronological day in the season while predicting RPE. Specifically, for each standard deviation increase in GPS load, RPE went up by 0.0055 per day during the season suggesting that load had a higher impact on RPE as the season progressed. In contrast, the interaction of day by mental stress, sleep duration, and soreness continued to be stronger as the season progressed. Each linear mixed-effect model predicted a larger amount of variance when accounting for individual variations in the random effects.